Mental performance consultants: exploring the impacts of reflection during initial practice development. Issue 1 (2nd January 2021) - Kraft, Erin; Seguin, Cassandra M.; Culver, Diane M.
ABSTRACT: The use of reflection to assist students in developing their initial practice is evident in the literature in many fields when it comes to building a practice that is informed by theory. In this article, the authors explore Mental Performance Consultants' (MPCs) experiences with the practice of reflection during their participation in a higher education programme (with a focus on theory and practice) and while developing their initial consulting practices. Three MPCs (current and former students of the higher education programme) participated in a semi-structured interview which was subsequently followed by a second interview where they simultaneously drew a modified Rappaport timeline to illustrate their identity and professional development journeys. The authors used this data and a content analysis of participants' relevant coursework to create three portrait vignettes to represent the MPC's development journeys with specific focus on the impacts of reflective practice. Although reflective practice is well documented as an ongoing professional development tool for MPCs, the results of this article highlight the significance of utilizing reflective practice for self-growth, identity development, and autonomy in those crucial beginning years of becoming a professional.